Performance Evaluation of Routing Protocols in MANET: DSR/AODV - Katrina, Julaihi, Aisyah; Arun, Dr Kuruvikulam Chandrasekaran (Journal of Applied Technology and Innovation, 2020)
This paper presents the comparative performance evaluation of routing protocols, specifically the Dynamic Source Routing (DSR) and Ad hoc On-Demand Distance Vector (AODV) protocols, in Mobile Ad hoc Network, commonly known as MANET. The goal of this paper is to determine which of these reactive or on-demand routing protocols are superior compared to the other, with variables integrated in the NETSIM simulation. Other than that, it is also aimed to prove whether the results achieved are true to the previous studies that have been done with similar properties and application settings. However, compared to the common amounts of nodes of 50 and above, the outcome of this simulation will contribute to the studies consisting of a lesser number of intermediate nodes and implementing a variable of the power source as it may show a difference considering one of the downsides of MANET is the limited power source of the intermediate nodes. This paper also gives way to future studies possibly with different properties integrated as technology continuously resumes its advancements.